SINTESIS SURFAKTAN METIL ESTER SULFONAT DARI METIL ESTER MINYAK BIJI KARET (Havea Brasiliensis) MELALUI REAKSI SULFONASI DENGAN PENGARUH VARIASI KATALIS - May Budiono; Aman Sentosa Panggabean (PROSIDING SEMINAR KIMIA, 2017)
Synthesis Methyl Ester Sulfonate ( MES ) from Karet seed oil methyl ester (Havea Brasiliensis.) through sulfonation reaction have been carried out. The results showed Karet seed oil content 46,45%, acid value 9,79623 mg KOH/ g oil and ALB levels of 4,92343%. First Bintaro seed oil is converted into methyl esters through an esterification process with variation of oil and methanol ratio at 1 : 6 using 4 % H2SO4 catalyst, in order to obtain a decrease in acid number of 3,60333 %. The results of GC-MS analysis showed the composition of the most dominant methyl ester is methyl linoleate by 34,19%. Synthesis sulfonation performed by reacting of methyl ester with variants 40%, 60%, and 80 % H2SO4 at a mole fraction ratio of 1 : 1.4 by varying the length of sulfonation time of 90 minutes, purification was performed using methanol 60 % v/v and H2O2 3 % v/v, with neutralization using 20 % NaOH. Sulfonation process is done using methods reflux. The optimum condition of synthesis of MES is sulfonation time reaction at 90 minutes, with the acquisition value of the voltage drop in the water level of 46,7728%. FT-IR spectra provide specific absorption peak for the group -C - O of an ester which characterize the existence of the MES as an ester compound at wave number 1168 cm- 1. It can be concluded that the compound is methyl ester sulfonate . Keywords : Karet Seed Oil , Esterification , Sulfonation , Methyl Ester Sulfonate